Contribution of Coach Social Support to Athletes Peak Performance After Major Injury - Prima Aulia (Universitas Negeri Padang, 2022)
This research is motivated by the results of previous research on the factors that influence the peak performance of athletes after severe injury, where there are five factors, namely experiencing a serious injury, namely the self-confidence factor, serious factors in training, the coach's social support factor, time / place disorientation factor, and factors focus. Of the five factors, four factors originate from the athlete himself, while one factor comes from outside the athlete, namely the coach's social support factor. Therefore, the researcher is interested in examining how much the contribution of this coach's social support to the peak performance of athletes after severe injury. After analyzing the data, it was found that there was a positive correlation between Trainer Social Support and Peak Performance with R = 0.486 with a significance level (sig 2 tailed) of 0.000. This means that the greater the coach's social support, the better their peak performance will beFurthermore, the results of the R Square of these two variables show a number of 0.237 which means that the social support of the coach has a contribution of 23.7% to restore peak performance of athletes after major injuries, while 76.3% is influenced by other factors not examined.